Volunteer survey effort for high-profile species can benefit conservation of non-focal species. Issue 2 (9th February 2017) - CROCKFORD, NICOLA J.; BUCHANAN, GRAEME M.
Summary: The last irrefutable record of the Critically Endangered Slender-billed Curlew Numenius tenuirostris came from 1995. The range of the species is poorly known, but between 2009 and 2011, volunteer observers surveyed more than 680 sites in 19 countries, with additional search effort in a further 12 countries. Although there were no definite sightings (two birds that might have been Slender-billed Curlew were reported), there were other benefits. These included increased knowledge of species distributions and populations in seldom visited areas (over 500, 000 birds of over 400 species were observed), the identification of threats to at least 10 Important Bird and Biodiversity Areas, the identification of sites that could qualify as Important Bird and Biodiversity Areas, and capacity building and education through involvement with local survey teams and observers and finally recommendations for future surveys. Thus, these surveys demonstrate the potential benefits of volunteer field surveys for non-focal species.